Peran Guru Dalam Meningkatkan Minat Belajar Anak Pada Proses Pembelajaran Luring Pasca Pandemi di RA Labschool IIQ Jakarta - Puput Nurhayati; Hulailah Istiqlaliyah (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
The purpose of this study is to describe the role of teachers in increasing children's interest in learning in the post-pandemic offline learning process in RA. Labschool IIQ Jakarta. This research usesn types of qualitative research, in this approach it has a descriptive nature and is more likely to use analysis. Data collection is carried out by means of observation, interviews, and documentation. The data analisis techniques are data reduction, data presentation and conclusion drawing. The results of this study show that the role of teachers can influence the increasing interest in children's learning in the post-pandemic offline learning process in RA. Labschool IIQ Jakarta compared to online learning, this can be seen when learning takes place students are very enthusiastic and enthusiastic. Teacher RA. Labschool IIQ Jakarta has learned how its duties and roles are for early childhood. In addition, teachers have also used interesting and fun learning strategies and methods that are adapted to the age and circumstances of student.